Closed loop identification with model predictive control: a case study - Amjad, S. (2003)
Closed loop identification techniques based on autoregressive models (ARMA), state space models and neural networks for multivariable processes with MPC are investigated. The techniques are tested through computer simulations and ultimately on field data from a gas plant in Saudi Arabia, where MPC application is most challenging and perhaps most beneficial.